Change of Oral Mucus in Patients with Diabetes (Eurasian Medical Research Periodical, 2022)
This article talks about changes in the mucous membrane of the oral cavity in patients with diabetes. Diabetes mellitus is associated with a greater likelihood of developing certain oral mucosal disorders.